Unaccustomed high-mileage vs intensity training-related changes in performance and serum amino acid levels - Lehmann, M.; Mann, H.; Gastmann, U.; Keul, J.; Vetter, D.; Steinacker, J. M.; Haussinger, D. (International Journal of Sports Medicine, 1996)
To test the overtraining-related "imbalanced amino acid hypothesis" (19), the influence of an unaccustomed average 103 %.4 wk-1 increase in training mileage (ITV) on performance and on serum levels of individual amino acids (AAs) was examined in distance runners and controlled by an unaccustomed average 152%.4 wk-1 increase in tempo-pace and interval runs (ITI). Two mmol.l-1 lactate performance (2 LP) increased, 4 LP stagnated and total running distance (TD) decreased in the incremental test during ITV--which may indicate an ITV-dependent overtraining--in contrast to an ITI-related increase in 2 LP, 4 LP and TD. The summed serum AAs decreased in ITV (2744 +/- 534 vs 2933 +/- 663 umol.l-1; p < 0.05) in contrast to an ITI-related increase (3541 +/- 657 vs 3252 +/- 885 umol.l-1; p < 0.05) with an average 29% higher final summed AAs concentration during ITI (p < 0.05). During ITV 12 individual AAs decreased by 6-17%, 8 remained constant and 3 increased (Cys, Met, fTrp) by 6-19%, as opposed to an ITI-related increase in 16 AA by 6-55%. The observed ITV-related changes in serum AAs profile were smaller than after completing contests as a marathon, a 100 km-run or an ultra-triathlon. It may be concluded that the observed small changes in AAs profile or AAA/BCAA and AA/LNAA ratios only represent an epiphenomenon without recognizable influence on incremental test performance, since increases in fTrp/LNAA ratios (+28% in ITV vs +45% in ITI) were found to be related both to performance impairment (ITV) and improvement (ITI).